Determinants of Clinical Diphtheria After Sub National Diphtheria Immunization Days in 2012 at Bangkalan - Feranita Utama; Chatarina Umbul Wahjuni; Santi Martini (Universitas Airlangga, 2014)
The government held a diphtheria sub-national immunization week in 2012 to overcome the problem of diphtheria outbreaks in East Java Province. Bangkalan District is the district with the high incidence of diphtheria in East Java Province. This study aims to analyze the determinants of diphtheria events in Bangkalan District after the diphtheria sub-national immunization week in 2012. This study uses a case-control study design. Case samples were taken from a total of 31 cases, and control samples were taken as many as 124 people spread in 25 case villages and25 control villages. The bivariate analysis a using chi-square test and simple logistic regression. Multivariate analysis using logistic regression. The results showed that based on the results of bivariate analysis, individual and household levels related to diphtheria events, namely the status of Diphtheria Pertussis Tetanus (DPT) immunization, sub-national immunization week status, age and mother's education. Multivariate analysis showed that factors related to the diphtheria incidence in Bangkalan District after the 2012 diphtheria sub-national immunization week were DPT immunization (p = 0.012; OR= 4.765), incomplete DPT immunization (p = 0.001; OR = 6.276), age 3- 7 years (p = 0.014; OR = 15.137), ages 7-15 years (p = 0.001; OR = 41.984), and are not immunized at the time of sub-national immunization week (p = 0.020; OR = 3.553). The conclusion of this study is the DPT immunization status, age and status of diphtheria sub-national immunization week were the dominant factors affecting the incidence of diphtheria in Bangkalan District.